A Teacher's Code-Switching In English Classroom - Sri Kinanti Khairunnisa; Lidiyatul Izzah (Syntax Idea, 2022)
This study aims to look into different the types of code-switching that the teacher employs when teaching English at Al-Hidayah Boarding School and the function of the teacher's code-switching on English learning at Al-Hidayah Boarding School. This writer has conducted this study through a qualitative method with a case study design. An English teacher is a subject in this study. The writer has collected the data using observation and interview instruments. The results of the data analysis showed that the use of code-switching by the teacher in English teaching at Al-Hidayah Boarding School occurred in a total of 199 cases; (1) intra-sentential code-switching occurred 88 times, (2) inter-sentential code-switching 76 times, and (3) tag code-switching occurred 35 times. The function of code-switching used by the teacher found three functions; Topic switch, affective function, and repetitive function. The teacher used code-switching mostly to assist him in conveying material with repetitive functions to avoid misunderstandings.